Overview of mechanisms related to citrulline malate supplementation and different methods of high-intensity interval training on sports performance: A narrative review - Hadi Nobari; Laya Samadian; Saber Saedmocheshi; Pablo Prieto-González; Christopher MacDonald (Heliyon)
Regular exercise is a practical non-pharmacological approach to maintaining physical and mental health through rehabilitation and prevention of chronic diseases due to its cardiovascular, cardiorespiratory, neurological, and neuromuscular benefits. Despite awareness of the benefits of exercise, a “lack of time” has proven to be the most common impediment to regular activity. Thus, a time-efficient and potentially enjoyable training modality with growing popularity is high-intensity interval training (HIIT). HIIT incorporates intermittent bouts of work and recovery intervals performed at an intensity close to maximal oxygen consumption (VO2max). HIIT is considered to have equivalent or superior benefits compared to moderate-intensity continuous training (MICT). This narrative review focuses on the mechanisms of Citrulline Malate (CM) supplementation and various modes of HIIT on exercise performance. CM serves as a nitric-oxide enhancer leading to improved aerobic and anaerobic exercise performance by increasing muscle adenosine triphosphate (ATP) production, vasodilation, and blood flow to the active musculature and boosting work capacity. This article reviews the mechanisms related to CM supplementation and different modes of HIIT on exercise performance. Even though a single, acute 8 g dose of CM has been recommended, its mechanism of action remains to be seen due to the synergistic impact of both components (citrulline and malate). Moreover, the limited evidence for the standard level of supplement use and source of purchase results in athletes’ self-prescription of supplements. Therefore, to reduce the risk of accidental doping or toxicity, further studies should continue to investigate the optimal dose, timing, mechanism of action, as well as reliable sources of purchase for CM consumption.